2013
DOI: 10.3390/ijms14047155
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Analysis of Drought-Induced Genes in the Roots of a Tolerant Genotype of the Common Bean (Phaseolus vulgaris L.)

Abstract: In Brazil, common bean (Phaseolus vulgaris L.) productivity is severely affected by drought stress due to low technology cultivation systems. Our purpose was to identify differentially expressed genes in roots of a genotype tolerant to water deficit (BAT 477) when submitted to an interruption of irrigation during its development. A SSH library was constructed taking as “driver” the genotype Carioca 80SH (susceptible to drought). After clustering and data mining, 1572 valid reads were obtained, resulting in 112… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 54 publications
0
42
0
Order By: Relevance
“…Transcriptome analysis in common bean under drought stress using EST approaches showed contrasting expression patterns between tolerant and susceptible genotypes (Montalvo-Hernández et al 2008;Recchia et al 2013). Susceptible genotypes showed a marked down-regulation of aquaporins expression in response to drought, while resistant showed a stable or higher expression of these genes.…”
Section: ; Magadum Et Al 2013) Duplicated Genes Could Undergo Pmentioning
confidence: 99%
See 2 more Smart Citations
“…Transcriptome analysis in common bean under drought stress using EST approaches showed contrasting expression patterns between tolerant and susceptible genotypes (Montalvo-Hernández et al 2008;Recchia et al 2013). Susceptible genotypes showed a marked down-regulation of aquaporins expression in response to drought, while resistant showed a stable or higher expression of these genes.…”
Section: ; Magadum Et Al 2013) Duplicated Genes Could Undergo Pmentioning
confidence: 99%
“…Despite the possible importance of aquaporin in regulating drought stress response in common bean (Aroca et al 2006;Montalvo-Hernández et al 2008;Recchia et al 2013), none of the droughtQTLs identified by Mukeshimana et al (2014) are located near aquaporin loci. The response variables analyzed in the above-mentioned study were mainly related to flowering time, maturity, and seed productivity, suggesting that aquaporins could have only a marginal role in these developmental processes in common bean.…”
Section: ; Magadum Et Al 2013) Duplicated Genes Could Undergo Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding abiotic stress responses in plants is difficult due to the complexity, interrelationships, and variability of mechanisms and molecules involved. However, it is important to understand the mechanisms by which tolerant cultivars respond to stress in order to select genes that may be useful in rice breeding programs (Recchia et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The SSH method [76] consists on the hybridization of one cDNA population (tester -sample whose genetic profile is of interest, e.g., drought-tolerant genotype), with an excess of cDNA from a control population (driver -usually drought-susceptible genotype or well-watered control), followed by the separation of the nonhybridized molecules (target genes -the ones of interest) from the hybridized ones (what is common for both samples). In this session, we are aiming to present some of the results obtained by our group during the construction of a SSH library contrasting populations of cDNAs extracted from root tissues of two common bean genotypes, BAT 477 (tester -drought-tolerant) and Carioca 80SH (driver -drought-susceptible), both submitted to a 192 hours of water-deficit regime at the R5 developmental stage [77].…”
Section: Gene Expression Profiles From Subtractive Libraries Of Cdna mentioning
confidence: 99%